Increasing of forest raw material utilization in woodworking industry - Maksymiv, Volodymyr; Ferentc, Oleg; Manziy, Svitlana; Kopynets, Zoya; Ferentc , Andriy (Forestry, Forest, Paper and Woodworking Industry, 2007)
Scientifically based wood consumption specifications in timber production using horizontal band mill. Some problems of wood expenditure normalization in joiner’s wares have been discussed in this article.